Pengembangan LKPD Elektronik Guided Inquiry untuk Mereduksi Miskonsepsi dan Meningkatkan Keterampilan Penguasaan Konsep Peserta Didik SMA Pada Materi Gerak Lurus - M. Ibnusaputra; Insih Wilujeng; Heru Kuswanto (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop guided inquiry electronic worksheets that are suitable for use. Another objective is to determine the level of effectiveness of guided inquiry electronic worksheet products in reducing misconceptions and improving the mastering physics concepts in straight motion material. This Research and Development (R&D) research adapts the stages of development research from Borg and Gall. The research was conducted at SMAN 1 Gerung, West Lombok, West Nusa Tenggara. A total of 60 students in class XI MIPA for empirical trials of test instruments, and 94 students in class X MIPA for extensive trials. The data analysis technique uses 1 way ANOVA with advanced testing using partial ETA square for analyzing concept mastery, while misconceptions use Certainty Response Index (CRI) analysis. The results of expert validation on guided inquiry student worksheet development products, and supporting products in the form of lesson plans and conceptual mastery skills test instruments are included in the category of proper use and very valid. The empirical test results of the test instrument have also been categorized as valid. The application of guided inquiry electronic worksheet products based on CRI analysis effectively reduces misconceptions by 42.31%. Based on the results of the 1st ANOVA inferential statistical analysis, it was significant at 0.039, indicating that there were differences in concept mastery between students who applied guided inquiry worksheets and students in the control class. Further test results with partial ETA square also show the effectiveness of the product in the form of influence on concept mastery with a significant 0.039, which is a moderate leve